Pembelajaran Berdiferensiasi dan Praktik Baik Pelaksanaannya bagi Guru di SMA Negeri 1 Sumberpucung - Farid Wahyudi; Priska Choirina; M. Rizal Akbar Zam Zami; Purwatiningsih Purwatiningsih; Lia Damayanti; Anggraeni Hadi Pratiwi; Urnika Mudhifatul Jannah; Pangestuti Prima Darajat (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Kurikulum Merdeka encourages schools to implement specific teaching to identify the interests of each individual. This study aims to provide different learning training for teachers in Sumberpuchung National 1 High School. This online training involves the presentation of materials, group discussions, and the sharing of good practices, using the SMALOKA learning community tools available on the Merdeka Teaching platform. The results of the training included the enthusiasm of many participants and the diversity of participants from different regions. In addition, there was an increase in teachers' understanding of differentiated learning concepts and their enthusiasm for applying them in the classroom. However, ongoing support is still needed to overcome the challenges in implementation. This research highlights the importance of collaboration between teachers in developing learning practices that are more inclusive and responsive to student needs.